2001
DOI: 10.1007/s004420100678
|View full text |Cite
|
Sign up to set email alerts
|

Habitat choice in Phylloscopus warblers: the role of morphology, phylogeny and competition

Abstract: We studied ecological and evolutionary aspects of habitat choice in a group of closely related bird species to gain insight into factors influencing bird community structure. Seven species of Phylloscopus warblers breed sympatrically in the middle taiga subzone of Central Siberia. We examine how the distribution of species among habitats is related to morphology, phylogeny and competition, and we compare our results with an earlier study on the ecomorphology of Phylloscopus warblers in Kashmir. We found that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 39 publications
2
27
0
Order By: Relevance
“…In line with our study, coniferous species tend to be smaller than deciduous species among the Phylloscopus warblers (Gaston 1974;Forstmeier et al 2001). The latter authors developed three hypotheses to explain such a relationship: (1) Small species may show a preference for coniferous habitats because small body size allows more efficient use of foraging techniques that are advantageous in coniferous vegetation, such as hovering flight and clinging to conifer-needles, (2) larger species may prefer habitats with on average larger prey items, which are found in deciduous trees (Nystro¨m 1991), and (3) smaller species might profit from the reduced interspecific competition in a coniferous habitat (Forstmeier et al 2001).…”
Section: Sizesupporting
confidence: 91%
See 2 more Smart Citations
“…In line with our study, coniferous species tend to be smaller than deciduous species among the Phylloscopus warblers (Gaston 1974;Forstmeier et al 2001). The latter authors developed three hypotheses to explain such a relationship: (1) Small species may show a preference for coniferous habitats because small body size allows more efficient use of foraging techniques that are advantageous in coniferous vegetation, such as hovering flight and clinging to conifer-needles, (2) larger species may prefer habitats with on average larger prey items, which are found in deciduous trees (Nystro¨m 1991), and (3) smaller species might profit from the reduced interspecific competition in a coniferous habitat (Forstmeier et al 2001).…”
Section: Sizesupporting
confidence: 91%
“…Within 16 Dendroica warblers of North America, the coniferous forest breeders are generally larger than deciduous forest breeders (Greenberg 1979). In contrast, among the Old World Phylloscopus warblers, the conifer-dwelling species have significantly lower body masses than the deciduous inhabitants (Gaston 1974;Forstmeier et al 2001).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Wing length was found to be associated with migration distances in long-distant migratory birds (Tarka et al 2010), which may indicate its importance in flight ability and survival. Wing size is also a signal for dominance among males in reed passerines (Nowakowski 2000, Forstmeier et al 2001, which can thus be used as a correlate of the quality of the breeding habitats (Johnson 2007). Furthermore, Alatalo et al (1985) and Rayner (1988) suggested that habitat structure can have selective effects on wing sizes at microevolu-tionary time scales.…”
Section: Introductionmentioning
confidence: 99%
“…The constraints that limit or prevent individuals from occupying those habitats where they could achieve greater fitness may be classed as evolutionary or ecological. Evolutionary constraints include all those that weight heavily on the biology of a species, such as its phylogeny or its life history traits (Forstmeier et al 2001). Ecological constraints include those arising from the landscape and biotic environment in which the species occurs.…”
Section: Introductionmentioning
confidence: 99%